Applicability of Sustainable Construction in Nigeria Infrastructure Projects-Empirical Study of The Six Geopolitical Zones - Adindu, Chinedu; Musa, Adamu; Nwajagu, Uchenna; Yusuf, Saheed; Yisa, Susan (CSID Journal of Infrastructure Development, 2020)
Despite the socio-economic importance of the Built Environment (BE) industry; its resources and products regrettably impact the host environment negatively, necessitating a departure from traditional to Sustainable Construction (SC) methods. Lack of SC awareness has been identified by several researchers as a major impediment to its adoption in Nigeria. This study, therefore, assessed the level of SC awareness, examined the sources of SC knowledge, and determined ways of improving SC applicability in Nigeria. The descriptive survey research methodology was used and a structured questionnaire administered purposively to 171 BE professionals, with 133 valid responses, hence a 78% success rate. The results of the study showed that all the states in the six geo-political zones fell below the geopolitical zone mean awareness index (GZMAi) value of 0.700; a poor contribution of current academic curriculum, and poor site experience arising from paucity of SC knowledge on projects, as hindrances to its applicability. The study concludes that the characteristic low knowledge level of SC amongst BE professionals are institutionally based, and therefore, recommends adoption of global sustainability standards, increased sensitization of SC techniques via seminars and training workshops, the inclusion of SC in tertiary education curriculum, and in the certification programmes of BE professional institutions, amongst others